(untitled) (Jahangirnagar University Journal of Biological Sciences, 2016)
Indigenous knowledge on the utilization of Blumea lacera L. by the interim people as well as ethnic communities living at the vicinity of Sundarban mangrove forest of Bangladesh were documented through survey, interview, collection and identification. Native people of Sundarban use the herb in bleeding piles. Leaf of the plant was found to be the most useful part for ethnomedicinal use. Generally, leaves of B. lacera have been used to treat most kinds of colds. Warm leaf paste used as diuretic whereas leaf paste with black pepper powder was found to apply in dog bite. Furthermore, B. lacera collected from Sundarban mangrove habitat as well as from natural plain land habitat (JU campus) were subjected to a comparative analysis of antibacterial activity. Antibacterial study from the present experiment suggested that the ethyl acetate fraction of B. lacera, irrespective of habitat choice, was active against the gram-positive bacteria Bacillus cereus. The methanol fraction of Sundarban sample showed significant dose dependent increase in antibacterial activity against the gram-negative bacteria Serratia sp., Proteus mirabilis, Salmonella typhi and Vibrio cholera while the JU sample did not produce any inhibition zone. The n-hexane fractions of both type plant samples were entirely non-responsive to the bacterial growth. Jahangirnagar University J. Biol. Sci. 3(2): 17-24, 2014 (December)